MODEL PENATAAN REKLAME PEREMPATAN JALAN KOTA YOGYAKARTA - , MASHURI, ST, Ir. Ahmad Sarwadi, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Growth in economic activity in cities to support the growing media launches ad products in the community in which one of them by advertising (signage). Crossing is a strategic point in the city where the meeting point of several roads that intersecton, can be accessed from many directions, and many adopted the general public. Also, having so traffict at intersecton light to make the car stop for a moment that allows the driver to see billboards located around the intersectonion of the road. In the presence of a strategic crossroads, making the region one of the location screen. Signs of growth are not directed / planned, provide a "pressure area" and impacts "visual distortion" at the crossroads of Yogyakarta City. Thus, we need good models of structuring the display at the intersectonion of roads to create visual comfort Yogyakarta City. Type the location of billboards is an appropriate method for structuring "Reklame Yogyakarta crossroads" because of many possible intersectonions with similar characteristics. To get the model number of samples was done by classification of fires, which have similar characteristics. Each of each of these characteristics makes the choice of sampling model for studying the visual character of each model as standard. visual character of quality research methods billboards in every corner of the sampling model questionnaire and observation of the theory developed by Robert Kreda with parameters: readible and legible, harmony with the building, aestetically, appropriate and scale. Research results are 9 specifications of existing intersectonions in the city of Yogyakarta. The conclusions on the visual character sign Yogyakata crossroads city feels trend Yogyakarta visual distortion. This conclusion is based on research and application results observation and there was no significant difference in the results of these two lines of research. Trend parameters of the intersection that getting visual distortion are harmony with the building and aestetically. Signage arrangement model of Yogyakarta City is made consider to things like: intersection and advertisement item.